Population Status and Distribution of Gharial (Gavialis gangeticus) in Nepal - Thapaliya, Bishnu P; Khadka, Madhav; Kafley, Hemanta (The Initiation, 2010)
Gharial (Gavialis gangeticus), biological treasure of the Indian subcontinent now restricts its existence in few big river systems of India and Nepal only. Innumerable threats posed to Gharial and its natural habitat led to extinction of the species from Bhutan, Burma and Pakistan and almost extinct from Bangladesh. Despite of the concerted Gharial conservation effort of Nepal and India since midtwentieth century, the species finds its status as Critically Endangered on the IUCN 2007 Red list. Realizing the fact that a basic step in any conservation plan involving mega herpetofauna is to estimate its population status and structure and its geographic distribution, Department of National Parks and Wildlife Conservation (DNPWC) and World Wildlife Fund (WWF) Nepal held Gharial census on January-February 2008. The census estimated a total of 81 Gharials in Nepal. Out of total Gharial recorded during the census, 70 Gharials were recorded through direct sighting while 11 were based on indirect observations. Factors responsible for decreasing Gharial population were flood and dam construction, habitat destruction and decline in food quality & quantity. Over fishing, use of gill nets and river poisoning adversely affected the quality and quantity of fishes that serve as main food for Gharial. Contradictory to the past findings decreasing Gharial population was not attributed to the illegal egg collection and poaching of male Gharial for "Ghara". Deliberate killing was only found to take place in case the animal got entrapped in fishing nets. We conclude that Gharial should receive high conservation priority in future too. Efforts to restore the population through artificial breeding have much to do for maintaining present population. However, declining population, despite of several Gharial releases, should be addressed through more detailed scientific study. Census should be based on direct sighting through extensive field observation. Gharial release should precede scientific field study for assessing habitat suitability and follow with intensive monitoring program. The emphasis should be given for preparing specific Gharial Conservation Action Plan for regulating conservation activities to help conserve Gharial in Nepal. Key Words: Gharial conservation, Population status, Captive breeding, Threats DOI: 10.3126/init.v3i0.2422 The Initiation Vol.3 2009 p.1-11